Development of a Special Service Tool for Hydraulic Piston Maintenance on Excavator PC 210-10M0 - Armas, Reza Febriano; Purwono, Hendro; Junaedi, Thomas; Alfauzi, Alfauzi; Santosa, Lintang Fuji (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2024)
Excavators are essential machinery widely utilized in mining, construction, plantation, and other industries. The Komatsu PC210-10M0, a small-sized excavator model, performs critical operations such as material digging and transportation. However, during component overhauls, particularly for the boom cylinder, bucket, and arm, significant challenges arise due to the absence of suitable tools for efficiently removing and installing hydraulic cylinder pistons. The current reliance on generic tools such as screw wrench sets (L-keys) is suboptimal, leading to inefficiencies, increased risks of workplace accidents due to tool slippage, and longer processing times. This study addresses these limitations by employing the Seven Up++ method to develop a specialized service tool specifically designed for hydraulic cylinder piston maintenance. The methodology encompasses three critical phases: Analysis, Solution, and Results, ensuring a systematic and innovation-focused approach. The developed tool securely positions itself on the piston cylinder, utilizing two pins inserted into pre-existing holes on the piston surface. The results demonstrate significant improvements: maintenance processing time is reduced by up to 70%, operational safety is enhanced due to the tool's secure attachment, and labor requirements are halved, with manpower reduced from two operators to one. These findings highlight the tool's potential to optimize maintenance operations and improve overall efficiency in the use of Komatsu PC210-10M0 excavators.